Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

Janus graphene oxide membrane with rational allocation of functional regions as unidirectional ion valve system - Jundong Yan; Lingfeng Liu; Zhichen Liang; Chongfeng Huang; Wenbiao Zheng; Changsheng Guo; Minchao Liu; Chao Peng; Jianbo Jia; Mengchen Zhang (Desalination, 2024)

Hormone and reproductive factors and risk of systemic lupus erythematosus: a Mendelian randomized study - Runyu Chang; Shate Xiang; Yibo Jin; Xiaofen Xu; Suhai Qian; Lingfeng Chen; Chao Hu; Yufeng Shi; Xinghong Ding (Immunologic Research, 2024)

Experimental and modeling study of ignition delay times of n-C5H12 and C3H6 under O2/CO2 atmospheres - Chao Peng; Chun Zou; Jiaxin Ren; Qianjin Lin; Wenxiang Xia; Lingfeng Dai; Jiacheng Liu; Wenyu Li (Fuel, 2024)

EEG-FRM: a neural network based familiar and unfamiliar face EEG recognition method - Chao Chen; Lingfeng Fan; Ying Gao; Shuang Qiu; Wei Wei; Huiguang He (Cognitive Neurodynamics, 2024)

Low-photovoltage-loss pringting perovskite solar cells in ambient air through ink synergistic engineering - Yifan Lv; Kaiyu Wang; Ai Lan; Lingfeng Chao; Changshun Chen; Jinpei Wang; Qing Yao; Jianxin Chen; Tengfei Pan; Yajing Li; Hui Zhang; Yingdong Xia; et al. (Chemical Engineering Journal, 2023)

Quenching-induced surface reconstruction of perovskite oxide for rapid and durable oxygen catalysise - Lingfeng Ke; Shengli Pang; Chao Long; Ting Fang; Gongmei Yang; Yifan Song; Xudong He; Shuai Ma; Yaozheng Qian; Xiangqian Shen; Chonglin Chen (Chemical Engineering Journal, 2023)

Halide-chalcogenide hetero-structure for efficient and stable perovskite solar cells - Riming Nie; Zeliang Wei; Aarti Mehta; Lingfeng Chao; Jiaxing Gao; Weicun Chu; Zhongping Li; Han Miao; Yonghua Chen; Wanlin Guo (Chemical Engineering Journal, 2023)